Penerapan Pendekatan Restoratif dalam Pengelolaan Disiplin Siswa Melalui Kemitraan Manajemen Sekolah dan Komite Sekolah di SMA Negeri 4 Maluku Tenggara - Paulus Berakmans Rettob; Nur Shauma Apriani; Nuri Imelda Sari; Ika Pratiwi (Jurnal Sosial Humaniora dan Pendidikan, 2026)
The purpose of this study is to analyze how the implementation of a restorative approach in the management partnership between the school and the school committee influences student discipline at SMAN 4 Southeast Maluku. The restorative approach is an alternative form of discipline to punitive disciplinary practices, focusing on relationship repair, responsibility, and students’ social reintegration, as stated by Pranoto and Suwarjo (2021) and Hopkins (2016). This research employed a case study design with a descriptive qualitative approach. Data were collected through in-depth interviews, participatory observation, and documentation studies involving the principal, teachers, student representatives, and school committee management. The results indicate that there is a synergistic partnership between the school and the school committee in implementing restorative practices, such as peer mediation, restorative circles, and disciplinary conferences. These practices were effective in reducing repeated disciplinary violations, increasing students’ sense of responsibility, and fostering an inclusive, participatory, and respectful school climate. It can be concluded that strong collaboration between the school and the school committee is a key factor in the successful implementation of a restorative approach to discipline as an educational process for the school community.